Ciliate symbionts of bivalves with notes on their worldwide geographic distribution - Mayén-Estrada, Rosaura; Dávila, Sthefane; Dias, Roberto Junio Pedroso (Zootaxa, 2024)
The shells, mantle cavities and various organs of mollusks serve as suitable habitats for symbiotic ciliates, as commensal, epibiotic and parasitic. With about 80,000 species, molluscans are distributed in freshwater, marine and terrestrial habitats; symbiotic ciliates have been recorded in bivalves, gastropods and polyplacophorans; however these records have not been integrated in comprehensive revisions. The goal of this work is to provide an updated checklist of the ciliates involved as symbionts of bivalve molluscs worldwide. Available records of symbiotic species of ciliates were compiled and checked, along with their molluscan hosts and localities. We obtained data for 165 species of ciliates as symbionts of 158 bivalve hosts, distributed in 31 countries, regions and seas. This is the first comprehensive study to review the biodiversity of ciliates associated with bivalves and show that only a small fraction of this class of molluscs has been studied in terms of their symbiotic relationships with ciliates.